Dopamine uptake sites in the striatum are distributed differentially in striosome and matrix compartments. - Graybiel, A M (1989)
A major mechanism of neurotransmitter inactivation at catecholaminergic synapses is reuptake of released transmitter at high-affinity uptake sites on presynaptic terminals. We have analyzed the anatomical distribution of site-selective ligand binding for dopamine uptake sites in the striatum of rat, cat, and monkey. We report here that desipramine-sensitive [3H]mazindol binding sites have highly heterogeneous distributions in the dorsal and the ventral striatum. In the caudate nucleus of cat and monkey, [3H]mazindol binding observes striosomal ordering, being reduced in striosomes and heightened in the extrastriosomal matrix. Some local heterogeneity appears in the ventral caudoputamen of the rat. Different subdivisions of the nucleus accumbens also have different binding levels. These findings suggest that some functional effects of psychoactive drugs, such as cocaine, that bind to the dopamine-uptake complex could be related to the distribution of these specific uptake sites. The findings also raise the possibility that these distributions could result in selective neuronal vulnerability to neurotoxins, such as 1-methyl-4-phenylpyridine (MPP+), that depend on the dopamine-uptake complex for entry into neurons.